Drafting sex workers' human rights: using decriminalisation to combat gender-based violence faced by sex workers - Singh, Kiasha (Department of Public Law, 2025)
Rates of gender-based violence (“GBV”) are rapidly growing in South Africa, which has come to be known as the “rape capital” of the world. 1 This violence is indiscriminately perpetrated against women across the country, including sex workers who are often victim of heinous acts of GBV due to their limited protection under the law and stigmatised role in society. The legal responses to sex work, namely legalisation, criminalisation, or decriminalisation, have become an increasingly discussed topic across the world due to a heightened understanding of the complex challenges sex workers face. While it is currently illegal to buy or sell sex in South Africa, if the Criminal Law (Sexual Offences and Related Matters) Amendment Bill 2022 (“the Bill”) is passed, South Africa will become only the third country in the world to fully decriminalise sex work. The draft Bill proposes the removal of the criminalisation of buying and selling of sex and the clearing of criminal records of those who have been prosecuted for buying or selling sex. This dissertation is therefore, aimed at critically analysing how decriminalising sex work in South Africa by way of enacting the draft Bill can aid in reducing sex workers' vulnerability to experiencing GBV, specifically by affording greater protection to sex workers and eradicating the dangerous stigma around sex work. This dissertation therefore undertakes to investigate how the criminalisation of sex work disproportionately affects sex workers by exposing them to rampant levels of abuse, sexual violence and police brutality, under the umbrella of GBV. Therefore, it further aims to establish how the criminalisation of sex work correlates directly with the violation of numerous sex workers' human rights. In considering how effective South Africa's current legal response to sex work is, it is pertinent to analyse our international and domestic obligations to protect women against violence and violations of their human rights, specifically identifying the position of sex workers amongst these protective forces. In bolstering attempts to protect the rights of sex workers and give effect to the intentions of the Bill of Rights and South Africa's international obligations, the findings of this dissertation ultimately reveal why it is of the utmost importance that government decriminalise sex work and enact the Bill without undue delay. Further recommendations will be provided to work in conjunction with the draft Bill to assist the safety of sex workers in South Africa.